2019
DOI: 10.4236/jss.2019.79002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Pet Ownership, Pet Attachment and Decision to Have Children among Single People in the United States: A Need for Flexible Child Care Facilities in the United States

Abstract: Research has found that as pet ownership increases, fertility declines in the United States. Many single people have lost interest in growing families due to high cost of child care and lack of time. Other people speculate that it is easier to manage pets than children and pets give them more freedom than children. The main objective of this research therefore was to find out through Bowlby's attachment theory the extent to which preference to pet relates with other variables like pet attachment, security, los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Most studies suggest that the primary reasons both cats and dogs are kept as pets is for companionship and affection, 12 - 17 with a large proportion of cat and dog owners (typically 70-90% or more) regarding their pet as a family member and exhibiting a strong human-animal bond. 12 , 16 , 18 - 24 Although not always the case, many studies have also found positive associations between pet ownership and improved physical and mental health in owners, 16 , 19 , 20 , 25 - 33 with evidence that a greater attachment to a cat may lead to greater health benefits.…”
Section: Human-animal Bond and Cat Ownershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies suggest that the primary reasons both cats and dogs are kept as pets is for companionship and affection, 12 - 17 with a large proportion of cat and dog owners (typically 70-90% or more) regarding their pet as a family member and exhibiting a strong human-animal bond. 12 , 16 , 18 - 24 Although not always the case, many studies have also found positive associations between pet ownership and improved physical and mental health in owners, 16 , 19 , 20 , 25 - 33 with evidence that a greater attachment to a cat may lead to greater health benefits.…”
Section: Human-animal Bond and Cat Ownershipmentioning
confidence: 99%
“…10 Similarly, a Growth from Knowledge Survey published in 2016 found that in 8/22 (36%) countries surveyed, there were a higher number of cat-owning households than dog-owning households. 11 Most studies suggest that the primary reasons both cats and dogs are kept as pets is for companionship and affection, [12][13][14][15][16][17] with a large proportion of cat and dog owners (typically 70-90% or more) regarding their pet as a family member and exhibiting a strong human-animal bond. 12,16,[18][19][20][21][22][23][24] Although not always the case, many studies have also found positive associations between pet ownership and improved physical and mental health in owners, 16,19,20,[25][26][27][28][29][30][31][32][33] with evidence that a greater attachment to a cat may lead to greater health benefits.…”
Section: Human-animal Bond and Cat Ownershipmentioning
confidence: 99%